Tax Implications Of E-Commerce Transactions: An Indonesian Legal Approach - Ratih, Lastika Dewi Anggoro; Putri Anggia (Fakultas Hukum Universitas Mataram, 2024)
This study explores the intersection of e-commerce and civil law in Indonesia, focusing on the implications for tax collection. Employing a normative legal research approach, the study draws on primary and secondary legal materials sourced through extensive library research. The qualitative data analysis is conducted using a descriptive analytical method. The findings underscore that e-commerce transactions are predominantly governed by electronic contracts, as stipulated in Article 1320 of the Civil Code and further regulated by the Electronic Information and Transactions Law (EIT LAW) No. 19 of 2016. These electronic contracts enable efficient transactions, eliminating the need for physical meetings. Central to these transactions are consumer rights, including the protection of accurate information and personal data, as mandated by the Personal Data Protection Law (PDP LAW) No. 27 of 2022. In terms of tax collection, e-commerce is subject to regulations under the Income Tax Law, VAT Law, and specific Ministry of Finance regulations. These regulations require certain digital service providers to collect Value-Added Tax (VAT) on transactions, ensuring compliance with national tax laws. The civil context of e-commerce in Indonesia is shaped by two key aspects: electronic contracts and their legal validity. Electronic contracts, which are generated, agreed upon, and signed through digital platforms such as email, web-based applications, and online contract management systems, streamline business processes by significantly reducing the time and costs associated with traditional transactions.